Die Lehre von der Oikonomia Gottes in der Oratio catechetica Gregors von Nyssa - Kees, Reinhard Jakob. (Vigiliae Christianae, Supplements, 1995)
This volume deals with Gregory of Nyssa's († 394 C.E.) soteriology as set forth in his handbook for catechetes. In part I-III the aim, method and structure of the Oratio catechetica are examined and the results are compared with Gregory's examples (Origen, Athanasius). Part IV presents the relationship between his theology ( theologia ) and soteriology ( oikonomia ) as well as the interrelated topics of that soteriology, thus describing the concept of oikonomia in the Oratio catechetica . Part V contrasts this concept with earlier works of Gregory and shows the developments of his thought. Part VI compares the teachings of Gregory with those of Methodius and Athanasius. The book is important for all those interested in early Christian thought and literature.